Modulation of TRPV4 by diverse mechanisms. (September 2016) - Darby, W.G.; Grace, M.S.; Baratchi, S.; McIntyre, P.
Abstract: Transient receptor potential ion channels (TRP) are a superfamily of non-selective ion channels which are opened in response to a diverse range of stimuli. The TRP vanilloid 4 (TRPV4) ion channel is opened in response to heat, mechanical stimuli, hypo-osmolarity and arachidonic acid metabolites. However, recently TRPV4 has been identified as an ion channel that is modulated by, and opened by intracellular signalling cascades from other receptors and signalling pathways. Although TRPV4 knockout mice show relatively mild phenotypes, some mutations in TRPV4 cause severe developmental abnormalities, such as the skeletal dyplasia and arthropathy. Regulated TRPV4 function is also essential for healthy cardiovascular system function as a potent agonist compromises endothelial cell function, leading to vascular collapse. A better understanding of the signalling mechanisms that modulate TRPV4 function is necessary to understand its physiological roles. Post translational modification of TRPV4 by kinases and other signalling molecules can modulate TRPV4 opening in response to stimuli such as mechanical and hyposmolarity and there is an emerging area of research implicating TRPV4 as a transducer of these signals as opposed to a direct sensor of the stimuli. Due to its wide expression profile, TRPV4 is implicated in multiple pathophysiological states. TRPV4 contributes to the sensation of pain due to hypo-osmotic stimuli and inflammatory mechanical hyperalsgesia, where TRPV4 sensitizaton by intracellular signalling leads to pain behaviors in mice. In the vasculature, TRPV4 is a regulator of vessel tone and is implicated in hypertension and diabetes due to endothelial dysfunction. TRPV4 is a key regulator of epithelial and endothelial barrier function and signalling to and opening of TRPV4 can disrupt these critical protective barriers. In respiratory function, TRPV4 is involved in cystic fibrosis, cilary beat frequency, bronchoconstriction, chronic obstructive pulmonary disease, pulmonary hypertension, acute lung injury, acute respiratory distress syndrome and cough.In this review we highlight how modulation of TRPV4 opening is a vital signalling component in a range of tissues and why understanding of TRPV4 regulation in the body may lead to novel therapeutic approaches to treating a range of disease states.